Complex Dietary Protein Improves Growth Through a Complex Mechanism of Intestinal Peptide Absorption and Protein Digestion. (January 2015) - Hansen, Stephanie A.; Ashley, Aaron; Chung, Brian M.
Background : The small intestinal epithelium has an impressive ability to adapt to changes resulting from loss of length or alteration in dietary load. We sought to determine the potential influence of dietary protein absorption on growth and development. We hypothesized that a complex protein diet would improve growth over that of an elemental diet. Methods : Using the nematode Caenorhabditis elegans, a transparent worm with a rudimentary intestinal tube lined by enterocytes that function remarkably similar to humans, we measured daily growth, intestinal peptide, and amino acid transporter expression and intestinal proteolysis to compare the effects of a complex protein diet to a diet containing only amino acids. Results : Nematodes raised on a complex protein diet grew to adulthood faster than those raised solely on amino acids, which did not require an overall change in intestinal peptide or amino acid transporter expression. Despite no overall change in transporter expression, a shift in location of peptide transporter expression was noted between diets that corresponded to decreased rate of intestinal proteolysis seen in the complex protein-fed group. Conclusions : A complex protein diet stimulates in an altered pattern of intestinal peptide transporter expression and intestinal proteolytic activity that results in improved growth compared with a diet of elemental amino acids. This improved growth appears to be the result of increased efficiency of a smaller number of enterocytes. These data might be useful in targeting intestinal rehabilitation therapies for short bowel syndrome and other risk factors for intestinal failure.